The other Bennet sister [compact disc, unabridged] : a novel - Hadlow, Janice (Macmillan, 2020)
Ultimately, Mary's journey is like that taken by every Austen heroine. She learns that she can only expect joy when she has accepted who she really is. She must throw off the false expectations and wrong ideas that have combined to obscure her true nature and prevented her from what makes her happy. Only when she undergoes this evolution does she have a chance at finding fulfillment; only then does she have the clarity to recognize her partner when he presents himself, and only at that moment is she genuinely worthy of love.